KAJIAN PEMAHAMAN PETERNAK DAN PELAKU USAHA PRODUK PANGAN ASAL HEWAN TENTANG PENYAKIT ZOONOSIS DAN PENCEGAHANNYA DI KOTA KUPANG - Desi Biru; Annytha Ina Rohi Detha; Diana A. Wuri (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Zoonotic desease transmission can happen in every stage of animal-orign food production, from farm to table. This study is counducted to evaluate the understanding of farmers and animal-origin food product enterprises about zoonotic diseases and their prevention in Kupang City. The study was conducted 6 region with 200 respondents from farmers, 30 respondents from buthcers, 30 respondents from meat distributors, 30 respndents from meat seller and 30 respondents from food industry. The result than analyzed by descriptive analysis and than presented in graphics and tables. The result shows that the understanding of farmers and animal origin food product enterprise in Kupang City about zoonotic diseases is low so that their behavior, in attempt to prevent zoonoses, is not maximal. In farmers, 87,5% of farmers do not have a proper check up for their animal’s health and 30,5% of them still consume meat from sick and dead animals. In butchers, 80% of butchers do not have a hand-washing facility, 86,7% do not have a seperated room for meat and visceral handling, 96,7% do not use a proper foot-wear when working, and 43,3% of them stil use water from the river or from gutters. In meat distributors, 90% of them only use bike as vehicle for the distribution. In meat sellers, 96,7% of meat sellers allow their customer to directly touch the product, 80% do not have a hand-whashing facility and 100% of them do not have a refrigerator as a storaging vacility. In food industry, 90% of them have a good cleaning behavior, wash their hand with flowing water and soap, and have a refrigerator as storaging vacility. It can be conlcuded that food industry is the only stage with good behavior in atempt to prevent zoonotic desease transmission.